Response speeds of direct and securitized real estate to shocks in the fundamentals - Elias Oikarinen; Martin Hoesli; Camilo Serrano (Aboa Centre for Economics (ACE), 2010)
This paper contributes to the literature by identifying the response patterns of direct and indirect real estate returns to shocks in the market fundamentals. The response speeds are estimated with vector autoregressive models using TBI and NAREIT returns for the period 1994-2009 in the United States. To avoid the potential influence of different property mixes and of leverage on the dynamics, we use sector level data and deleveraged NAREIT returns. The findings indicate that REIT returns lead direct real estate returns even when catering for the property type and for leverage. Our estimations suggest that this lead-lag relationship is due to the sluggish reaction of direct real estate prices to unexpected changes both in the fundamentals and in REIT prices. The findings further suggest that the perceived lead-lag relations are not only due to the slow adjustment of sellers' reservation prices, but also due to the sluggish reaction of demand in the direct real estate market.
Keywords: G14; C32; 330; Vector Autoregressive Models; Generalized Impulse Response Functions; Direct Real Estate; Securitized Real Estate; Dynamics